Gene pathway development in human epicardial adipose tissue during early life - Ojha, Shalini; Fainberg, Hernan P.; Wilson, Victoria; Pelella, Giuseppe; Castellanos, Marcos; May, Sean; Lotto, Attilio A.; Sacks, Harold; Symonds, Michael E.; Budge, Helen (American Society for Clinical Investigation, 2016)
Studies in rodents and newborn humans demonstrate the influence of brown adipose tissue (BAT) in temperature control and energy balance and a critical role in the regulation of body weight. Here, we obtained samples of epicardial adipose tissue (EAT) from neonates, infants, and children in order to evaluate changes in their transcriptional landscape by applying a systems biology approach. Surprisingly, these analyses revealed that the transition to infancy is a critical stage for changes in the morphology of EAT and is reflected in unique gene expression patterns of a substantial proportion of thermogenic gene transcripts (~10%). Our results also indicated that the pattern of gene expression represents a distinct developmental stage, even after the rebound in abundance of thermogenic genes in later childhood. Using weighted gene coexpression network analyses, we found precise anthropometric-specific correlations with changes in gene expression and the decline of thermogenic capacity within EAT. In addition, these results indicate a sequential order of transcriptional events affecting cellular pathways, which could potentially explain the variation in the amount, or activity, of BAT in adulthood. Together, these results provide a resource to elucidate gene regulatory mechanisms underlying the progressive development of BAT during early life.